The Effect of Robotic Assisted Gait Training With Lokomat® on Balance Control After Stroke: Systematic Review and Meta-Analysis - Baronchelli, Federica; Zucchella, Chiara; Serrao, Mariano; Intiso, Domenico; Bartolo, Michelangelo (Frontiers in Neurology, 2021)
Introduction. Disturbances of balance control are common after stroke, affecting the quality of gait and increasing the risk of falls. Because balance and gait disorders may persist also in the chronic stage, reducing individual independence and participation, they represent primary goals of neurorehabilitation programs. For this purpose, in recent years numerous technological devices have been developed, among which one of the most widespread is the Lokomat®, an actuated exoskeleton that guide patient’s limbs, simulating a symmetrical bilateral gait. Preliminary evidence suggests that beyond gait parameters, robotic assisted gait training may also improve balance. Therefore, the aim of this systematic review was to summarize evidences about the effectiveness of Lokomat® in improving balance in stroke patients. Methods. Randomized controlled trials published between January 1989 and August 2020, comparing Lokomat® training to conventional therapy for stroke patients, were retrieved from seven electronic databases. Balance, assessed by means of validated clinical scales, was considered as outcome measure. The PEDro scale was used to evaluate the methodological quality of the studies. The study protocol was registered on PROSPERO (no. CRD42020197531). Results. After the removal of the duplicates, according to the inclusion criteria 13 studies were selected, involving 445 subacute or chronic stroke patients. 11 papers contributed to 3 meta-analysis. Favorable results for recovery of balance in stroke survivors treated with Lokomat® where showed using Time Up and Go (pooled mean difference = -3.40, 95% CI -4.35 to -2.44; p< 0.00001) and Rivermead Mobility Index as outcome measures (pooled mean difference = 0.40, 95% CI 0.26 to 0.55; p< 0.00001). Not conclusive results were found when balance was measured by means of the Berg Balance Scale (pooled mean difference = 0.17, 95% CI -0.26 to 0.60; p = 0.44). Conclusions. Overall, most studies have shown beneficial effects of Lokomat® on balance recovery for stroke survivors, at least comparable to conventional physical therapy. However, due to the limited number of studies and their high heterogeneity, further research is needed to draw more solid and definitive conclusions.